Hard-X-ray-selected active galactic nuclei – II. Spectral energy distributions in the 5–45 GHz domain. Issue 1 (24th June 2022) - Panessa, Francesca; Chiaraluce, Elia; Bruni, Gabriele; Dallacasa, Daniele; Laor, Ari; Baldi, Ranieri D; Behar, Ehud; McHardy, Ian; Tombesi, Francesco; Vagnetti, Fausto
ABSTRACT: A wide-frequency radio study of active galactic nuclei (AGN) is crucial to evaluate the intervening radiative mechanisms responsible for the observed emission and relate them with the underlying accretion physics. We present wide-frequency (5–45 GHz), high-sensitivity (few $\mathrm{{μ }Jy\, beam^{-1}}$ ), (sub)-kpc Jansky Very Large Array (JVLA) observations of a sample of 30 nearby ($0.003\, \le \, z\, \le \, 0.3$ ) AGN detected by the International Gamma-Ray Astrophysics Laboratory ( INTEGRAL )/Imager on Board the INTEGRAL Satellite (IBIS) at hard X-ray. We find a high detection fraction of radio emission at all frequencies, i.e. ≥95 per cent at 5, 10, and 15 GHz and ≥80 per cent at 22 and 45 GHz. Two sources out of 30 remain undetected at our high sensitivities. The nuclear radio morphology is predominantly compact, sometimes accompanied by extended jet-like structures, or more complex features. The radio spectral energy distributions (SEDs) of the radio cores appear either as single or as a broken power law, a minority of them exhibit a peaked component. The spectral slopes are either flat/inverted or steep, up to a break/peak or over the whole range. The sample mean SED shows a flat slope up to 15 GHz that steepens between 15 and 22 GHz and becomes again flat above 22 GHz. Significant radio–X-ray correlations are observed at all frequencies. About half of the sample features extended emission, clearly resolved by the JVLA, indicating low-power jets or large-scale outflows. The unresolved cores, which often dominate the radio power, may be of jet, outflow, and/or coronal origin, depending on the observed frequency.